TAHAPAN PERKEMBANGAN ANAK DAN PEMILIHAN BACAAN SASTRA ANAK - Burhan Nurgiyantoro (LPMPP Universitas Negeri Yogyakarta, 2005)
AbstractUniversally, various psychological aspects of children develop through certain stages according to their age level. They go through stages of intellectual,moral and emotional developments, stages of personality and language developments, and stages in the growth of their concept about stories. Each type of development is divided into specific stages. Piaget divides childrens intellectual development, for example, into four stages: the sensory-motor, pre-operational, concrete operational, and formal operational stages. These stages come in accordance with their age development.Each stage has characteristics distinguishing it from anya other stage. The difference in characteristics logically implies in turn a difference in their response to reading matter. Consequently, in selecting reading matter for children, one should consider their age in order to make the selection match their psychological development of children of a certain age level would make the reading matter become uncommunicative because it is too difficult for them or make it uninteresting and boring for them because it is too easy or too simple.Key words: psychological development, intellectual development, selection of reading matter